A Case of Right Ventricular Endomyocardial Fibrosis Presenting with Right Ventricular Failure in an Immunocompromised Patient - Ratul Ghosh; Biswajit Majumder; Shibsankar Sarkar; Somnath Maji (Journal of Clinical and Preventive Cardiology)
Endomyocardial fibrosis is a rare disease in India but an important cause of restrictive cardiomyopathy. A middle-aged nondiabetic nonhypertensive male presented to us with features of right heart failure. Echocardiography shows a grossly dilated right atrium, reduced right ventricular (RV) volume with thickened RV wall, and obliteration of the apex of the right ventricle along with severe low-pressure tricuspid regurgitation. There was mild thickening and obliteration of left ventricular apex also. Cardiac magnetic resonance imaging was attempted but could not be done as the patient had severe claustrophobia. He was diagnosed as HIV positive and was started on ART. The patient was managed conservatively with loop diuretics along with ACE inhibitors and spironolactone, and is now doing well with regular follow-up.